The Use of Copywriting Formulas to Strengthen the Knowledge and Skills of Micro, Small, and Medium Enterprises in Product Promotion - Widyastuti, Dhyah Ayu Retno (TRI DHARMA MANDIRI: Dissemination and Downstreaming of Research to the Community (Journal of Community Engagement), 2025)
Digital marketing has become a preferred strategy for business owners to promote their products and services. In practice, however, they face a significant challenge—the need for creativity and the ability to craft effective messages when using social media marketing platforms. At the same time, business owners come from diverse educational and skill backgrounds. This community service program was conducted by a facilitator team targeting Micro, Small, and Medium Enterprises in Kapanewon (District), Kalasan—the program aimed to enhance participants’ capabilities to remain competitive in the digital marketing era. Assistance was provided through training on how to compose communication messages using digital copywriting formulas. The methods used included lectures and group-based practice sessions. The results showed that participants were able to develop promotional messages using three formula approaches and effectively deliver these messages verbally before an audience, consistent with the written narrative style they had created. This activity successfully improved participants’ knowledge and skills in product promotion.